Analysis Of The Influence Of Work Environment, Discipline And Motivation On Job Satisfaction Of Vocational Education Institution Employees - Ristawati, Ristawati; Yulia Novita; Iswahyuningsih; Dewi Ratih Kusuma Wardani; Musran Munizu (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
The purpose of this study is to ascertain how work environment, work motivation, and work discipline affect teachers' job happiness. Researchers use the population of all teachers. One hundred teachers served as the study's sample. In this study, questionnaires, observations, and interviews were utilized to collect data. Validity and reliability tests are the kind of data quality assessments that were employed in this study. Multiple linear regression analyses are used in this study. Numerous significant conclusions on the variables influencing teachers' job happiness are presented by the analysis that was done. First, job happiness among teachers is influenced in part by work motivation. This suggests that the degree of job satisfaction among teachers is significantly influenced by their level of personal work motivation. Second, work discipline has an impact on teachers' job happiness to some extent. This demonstrates that the degree of discipline exhibited in completing tasks is a significant factor in determining the degree of job satisfaction experienced by teachers. Third, it has been demonstrated that a teacher's job happiness is somewhat influenced by their workplace. Teachers' levels of job satisfaction can be influenced by a variety of factors, including corporate culture, work facilities, and the quality of relationships among colleagues. Moreover, overall, the work atmosphere, discipline, and motivation all affect teachers' job satisfaction at the same time. These results highlight how intricately these many elements interact to shape teacher job satisfaction in certain educational settings. Gaining a deeper comprehension of these elements will enable actions to be taken to boost teacher job satisfaction and raise the standard of instruction they deliver.